Unaccompanied minors in Ireland: Current Law, Policy and Practice - Samantha Arnold; Muireann Ní Raghallaigh (Social Work & Society, 2017)
Ireland, as a country on the periphery of Europe, has not been significantly impacted by the current refugee crisis. The number of unaccompanied minors (UAM) arriving in Ireland is very low. Perhaps precisely because of this Ireland has had the opportunity to greatly improve its care provision for UAM. As such, it represents a particularly interesting case study regarding current law, policy and practice as regards this cohort. This paper outlines existing and new legislation, presents recent data on UAM and draws on the significant amount of research on UAM in Ireland.